EFFECTS OF DIFFERENT LEVELS OF VITAMIN E IN FEEDON THE PERFORMANCE OF BROILER CHICKS - M. Ibrahia, H.; Kassab , A.; A. Ubaid, J. (The Iraqi Journal of Veterinary Medicine, 1987)
One- day old broiler chicks were divided into four equal groups and given rations containing four different levels of dl-α -tocopheryl acetate (10, 40, 70 and 100 mg/kg of feed). Each ration was given’ to one group. Body weight was increased significantly in groups consumed rations containing 70 and 100 mg of dl-a tocopheryl acetate per kg of feed. Feed consumption has not. been increased in these two groups which give economic weight to the results. Tt is concluded that dl-α-tocopheryl acetate may be considered as growth promotor.